Ladder Arrangement Method for Stealth Design of Vivaldi Antenna Array - XiaoXiang He; SaiSai Huang; Teng Chen; Yang Yang (International Journal of Antennas and Propagation)
A novel stealth design method for X-band Vivaldi antenna arrays is proposed in this paper by ladder arrangement along radiation direction. Two-element array, eight-element array, and 3 × 7-element array are investigated in this paper. S parameters, RCSs, and radiation patterns are studied, respectively. According to the ladder arrangement of Vivaldi antennas presented, 16.3 dBsm maximal RCS reduction is achieved with satisfied radiation performance. As simulated and measured, results demonstrate that the effectiveness of the presented low RCS design method is validated.